Executive control is disturbed in schizophrenia: evidence from event-related potentials in a Go/NoGo task - Weisbrod, Matthias; Kiefer, Markus; Marzinzik, Frank; Spitzer, Manfred (Biological psychiatry, 2000)
Background: Schizophrenic patients suffer from cognitive and attentional deficits, particularly from failure of executive control functions. Methods: This study investigated the cortical organization of executive control in schizophrenic patients and healthy control subjects using event-related potentials (ERPs). Event-related potentials were collected while subjects performed an auditory Go/NoGo task that required response inhibition. To exclude stimulus discriminability and early stimulus processing to confound results, stimuli were adjusted to the subject’s individual discrimination ability and were presented in a simple and a difficult version. Results: Schizophrenic patients performed similar to control subjects in the Go condition but worse than control subjects in the NoGo condition that required response inhibition. Event-related potentials revealed the neurophysiological substrate of this dysfunction. In the Go conditions, both healthy control subjects and schizophrenic patients showed the same voltage pattern. In the NoGo condition, control subjects and patients showed similar cortical activation only during early processing (N2 time window). However, in later stages of processing (P3 time window), healthy subjects showed left lateralization of ERPs over frontal areas while schizophrenic patients did not. Conclusions: We conclude that schizophrenic patients exhibit deficient processing in a neuronal network, including left frontal areas, that is involved in later stages of executive control function.
Gesehen am 08.06.2021